Radioprotective effect of vitamin E on salivary glands after radioiodine therapy for differentiated thyroid cancer: a randomized-controlled trial. Issue 11 (November 2017) - Upadhyaya, Arun; Zhou, Pingping; Meng, Zhaowei; Wang, Peng; Zhang, Guizhi; Jia, Qiang; Tan, Jian; Li, Xue; Hu, Tianpeng; Liu, Na; Wang, Sen; Liu, Xiaoxia; et al.
Abstract : Objectives: This study aimed to examine the radioprotective effect of vitamin E on salivary glands after radioactive iodine ( 131 I) therapy in patients with differentiated thyroid cancer. Patients and methods: Eighty-two patients with differentiated thyroid cancer were enrolled in this study. They were divided randomly into four groups (control group: 22 cases, group A: 23 cases, group B: 22 cases, and group C: 15 cases) before postsurgical ablation therapy with 100 mCi 131 I. The patients in groups A, B, and C received vitamin E 100, 200, and 300 mg/day orally, respectively, for a duration of 1 week before to 4 weeks after 131 I therapy. Salivary gland function was assessed using salivary gland scintigraphy immediately before and 6 months after 131 I therapy. Uptake fraction (UF), uptake index (UI), excretion fraction (EF), and excretion ratio (ER) of each salivary gland were measured and compared. Results: On comparison between before and after 131 I therapy in the control group, there was a significant decrease in UF of both right and left parotid glands (all P <0.01). In group A, a significant increase in EF of the right parotid gland ( P <0.01) and UI of the right submandibular gland ( P <0.05) was found. In group B, there was a significant increase in UI of the right parotid gland and both submandibular glands (all P <0.01). In group C, there was a significant increase in UF of the left parotid gland ( P <0.05) and the right submandibular gland ( P <0.01). Also, there was a statistical increase in UI in both submandibular glands (all P <0.01). However, on comparing the changes in the post- 131 I therapy salivary scintigraphy parameters among the four groups, there was a significant difference in ΔUI of the right parotid gland ( P <0.05) and both submandibular glands (all P <0.01), as well as ΔER of the left parotid gland ( P <0.05) and ΔUF of the left submandibular gland ( P <0.05). Conclusion: Vitamin E exerts significant protective effects on the parotid and submandibular glands after 131 I therapy.